Patterns of Food Utilization by the Germinating Lettuce Seeds - Park, Won-Mok (1974)
The embryo excised from seed of Grand Rapids lettuce (Lactuca sativa L.) can be cultured in distilled water. Complete digestion of the endosperm and transfer of nutrients from the endosperm to the embryo occur in the germinating seed with fat as the source of food. The fat is utilized for respiration, synthesis of amino acids, and to a degree, converted to sucrose. (14)C-Glucose administered to the seed is quickly converted to sucrose in the endosperm and translocated to the embryo. Radioactivity associated with the glucose remains predominantly in the carbohydrate fraction, and much of it is incorporated into what is believed to be cell wall polysaccharides. Relatively little isotope is distributed in the amino or organic acids.